Stable and Selective Dehydrogenation of Methylcyclohexane using Supported Catalytically Active Liquid Metal Solutions – Ga52Pt/SiO2 SCALMS - Oshin, Oshin; Nair, Sharanya Sukumar; Taccardi, Nicola; Wolf, Moritz; Soegaard, Alexander; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2020)
The use of gallium-rich, Supported Catalytically Active Liquid Metal Solution (SCALMS) is a promising new concept to achieve catalysis with atomically dispersed active metal atoms. Expanding our previous work on short alkane dehydrogenation, we present here the application of SCALMS for the dehydrogenation of methylcyclohexane (MCH) to toluene (TOL) using a Ga52Pt alloy (liquid under reaction conditions) supported on silica. Cycloalkane dehydrogenation catalysis has attracted great attention recently in the context of hydrogen storage concepts using liquid organic hydrogen carrier (LOHC) systems. The system under investigation showed high activity and stable conversion of MCH at 450 °C and atmospheric pressure for more than 75 h time-on-stream (XMCH=15 %) with stable toluene selectivity (STOL) of 85 %. Compared to commercially available Pt/SiO2, the SCALMS system resulted in higher yields and robustness. Baseline experiments with Pt-free Ga/SiO2 under identical conditions revealed the decisive influence of Pt dissolved in the liquid Ga matrix.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Alloys; dehydrogenation; gallium; methylcyclohexane; platinum; supported catalysts

Top-down vs. bottom-up synthesis of Ga–based supported catalytically active liquid metal solutions (SCALMS) for the dehydrogenation of isobutane - Raman, Narayanan; Söllner, Jakob; Madubuko, Nnamdi; Nair, Sharanya Sukumar; Taccardi, Nicola; Thommes, Matthias; Haumann, Marco; Wasserscheid, Peter (Chemical Engineering Journal, 2023)
Supported catalytically active liquid metal solutions (SCALMS) catalysts consist of a liquid metal solution of an active metal (e.g., Pd, Rh, Pt, Ni) in a low melting metal (e.g., Ga, In, Sn) deposited on a porous support material. In the current study, we extend and optimize the recently developed top-down synthesis protocol (ultrasonication of gallium metal) to prepare GaPd, GaRh and GaPt SCALMS systems. We compare the morphological differences in the obtained catalyst materials achieved between this approach and the more traditional bottom-up synthesis protocol (in situ thermal decomposition of triethylamino-gallane complex) using electron microscopy. Moreover, the spatial distribution of the catalytically active material in the porous alumina support is evaluated using high resolution argon physisorption measurements. Both techniques strongly indicate that the bottom-up approach leads to a high degree of pore penetration while the gallium droplets are largely on the outer surface in case of the top-down method. Changes to the surface chemistry of the support were also investigated by means of NH3/CO2 temperature programmed desorption. All catalytic systems synthesized by the two synthesis methods, i.e., GaPd, GaRh and GaPt, were tested in a quartz, fixed-bed tubular reactor for isobutane dehydrogenation. All SCALMS materials, irrespective of their individual synthesis protocol, were significantly more active than their pure metal counterparts. The SCALMS catalyst prepared using the bottom-up approach showed initial productivity of 407 gbutenes molM–1 min−1, 832 gbutenes molM–1 min−1, and 963 gbutenes molM–1 min−1 for the GaPd, GaRh and GaPt respectively. These values represent more than twice the initial activity obtained with the top-down synthesized counterparts. This activity difference can be explained by the analytically determined difference in liquid metal droplet size distribution.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Coking; Dehydrogenation; Gallium; Liquid metal; SCALMS; Supported catalyst

Versatile strategy for homogeneous drying patterns of dispersed particles - Rey, Marcel; Walter, Johannes; Harrer, Johannes; Perez, Carmen Morcillo; Chiera, Salvatore; Nair, Sharanya Sukumar; Ickler, Maret; Fuchs, Alesa; Michaud, Mark; Uttinger, Maximilian; Schofield, Andrew B.; Thijssen, Job H. J.; et al. (Nature Communications, 2022)
After spilling coffee, a tell-tale stain is left by the drying droplet. This universal phenomenon, known as the coffee ring effect, is observed independent of the dispersed material. However, for many technological processes such as coating techniques and ink-jet printing a uniform particle deposition is required and the coffee ring effect is a major drawback. Here, we present a simple and versatile strategy to achieve homogeneous drying patterns using surface-modified particle dispersions. High-molecular weight surface-active polymers that physisorb onto the particle surfaces provide enhanced steric stabilization and prevent accumulation and pinning at the droplet edge. In addition, in the absence of free polymer in the dispersion, the surface modification strongly enhances the particle adsorption to the air/liquid interface, where they experience a thermal Marangoni backflow towards the apex of the drop, leading to uniform particle deposition after drying. The method is independent of particle shape and applicable to a variety of commercial pigment particles and different dispersion media, demonstrating the practicality of this work for everyday processes.
CRIS-Team WoS Importer:2022-06-10